Employment and wage effects of extending collective bargaining agreements - Ernesto Villanueva (IZA World of Labor, 2015)
In many countries, the minimum wages and working conditions set in collective bargaining contracts negotiated by a limited set of employers and unions are subsequently extended to all the employees in an industry. Those extensions ensure common working conditions within the industry, limit wage inequality, and reduce gender wage gaps. However, several studies suggest that those benefits come at the cost of reduced employment levels, especially during recessions. The income losses of workers who are displaced because of a collective contract extension can offset the wage gains among workers who keep their jobs.
Keywords: J23; J31; E24; 330; collective contracts; wage inequality; employment losses